DIVERSITAS JALUR BIOSINTESIS SENYAWA TERPENA PAD A MAKHLUK HIDUP SEB AGAI TARGET OBAT ANTTINFEKTIF - Andria Agusta (BERITA BIOLOGI, 2006)
Terpenoid is a fundamental cells constituent in living organisms. In living organisms, terpenoid biosynthesize via classical pathway of mevalonate and via deoxyxylulose diphosphate (DXP). The distribution patterns of both pathways are unique and specific in living organisms. In human and animal, terpenoid biosynthesize via mevalonate and IPP isomerase type I enzyme system. In plant, terpenoid biosinthesize via combination of the mevalonate and DXP pathways with IPP isomerase type I enzyme system. In parasitic protozoa like Plasmodium falciparum and in major human bacterial pathogen such as Mycobaclerium tuberculosis, Salmonella typhii and Helycobacter pylori, terpenoid biosynthesize via DXP and repeatitive IPP isomerase type II enzymesystem. The specific diversity of the terpenoid biosynthetic pathways in living organisms can use as targets for development ofnovel antiinfective drugs.